Pengembangan Keterampilan Budidaya Tanaman Hias Bagi Kelompok Wanita Tani Sebagai Upaya Mendukung Ekonomi Kreatif Desa - Santhyami, Santhyami; Agustina, Lina; Agustina, Putri; Astuti, Rina; Kusumadani, Annur Indra; Sari, Siti Kartika (LPPPM STAI Darul Hikmah Bangkalan, 2025)
Ornamental plant cultivation can be widely beneficial in boosting community economic growth. The ornamental plant business is part of creative economic development and is one way to increase farmers' income towards better purchasing power. Ornamental plant cultivation is considered to have high economic potential, as it can be done on limited land with relatively small capital and a wide market. This community service activity aims to improve the skills and economic independence of members of the Berkah Tani 2 Women Farmers Group (KWT) through training and assistance in ornamental plant cultivation. The program will be implemented in May 2025 using a participatory approach (Participatory Rural Appraisal) that emphasizes active community involvement in every stage of the activity. The stages of this activity are activity preparation, activity implementation, and evaluation, where evaluation is conducted through interviews and observations after the activity is carried out. The results of the activity showed an increase in participants' knowledge, as seen from their ability to explain the cultivation stages more accurately, an increase in skills, as shown by the success of most participants in practicing plant propagation and maintenance independently, and an increase in motivation, as seen from the members' initiative to increase the number of plants and start planning simple marketing. This activity is expected to become a model for sustainable horticulture-based community empowerment.